Creep modelling of P91 steel employing a microstructural based hybrid concept. (September 2018) - Yadav, S.D.; Scherer, T.; Prasad Reddy, G.V.; Laha, K.; Sasikala, G.; Albert, S.K.; Poletti, C.
Graphical abstract: Highlights: A hybrid concept is presented to model the creep behavior of P91 steel. Model is described by three types of dislocation densities and subgrain size. Model predicts not merely creep curves, but also ongoing microstructure evolution. Evolution of glide and climb velocities of dislocations are discussed for the first time. Abstract: In 9–12% Cr steels, tertiary creep stage is led by the synergistic effect of precipitate coarsening, substructure recovery and cavitation, therefore difficult to address it physically. Overcoming this problem to a certain extent, in present research work creep curves of P91 steel are modelled up to the onset of tertiary regime, based on a hybrid concept that couples a physical model to continuum damage mechanics (CDM) approach. The physical approach describes the microstructure evolution, CDM approach addresses the damage evolution and this combination enables to model up to the onset of tertiary creep stage. The aforementioned hybrid approach considers three types of dislocation densities explicitly, i.e., mobile, boundary and dipoles. Furthermore, the number density and size of precipitates in as-received condition is obtained from MatCalc software and incorporated in the model. The modelled creep curves are in good agreement with the experimental creep curves up to the onset of tertiary creep stage. The evolution of different dislocation densities, subgrain size and damage parameters are discussed thoroughly. The evolution of glide and climb velocities are also compared for the first time. From the investigated conditions, it is deduced that glide velocity dominates over climb and hence accommodating the creep strain. It must be further emphasized that the model predicts higher dislocation densities and smaller subgrain size at higher stresses, in accordance with empirical relationships.